The density and distribution of Pacific Oyster (Crassostrea gigas) in Krueng Cut, Aceh Besar. Issue 1 (November 2021) - Ramadhaniaty, M; Octavina, C; Putri, FA; Karina, S; Ichsan
Abstract: Crassostrea gigas is a Pacific oyster that has the largest size among the other oysters. This oyster is most often found because of its ability to adapt to a variety of environments. Krueng Cut is an estuary area that gets a lot of nutrient input from sea water because it is directly adjacent to the ocean. This condition makes this area has a high abundance of oysters with high fishing and antropogenic activities as well. The purpose of this study was to determine the density and distribution of the oyster population from 3 representative stations along the estuary area of Krueng Cut. The method used in this study is random sampling using a quadratic transect. The results show that the highest density is indicated by station 3 with 55.67 ind/m2 and the lowest density is indicated by station 1 is 40.33 ind/m2. These results indicate that the activities of residents, the entry of contaminants from antropogenic affect the density of oysters. The distribution of oysters from the three stations showed similarities, namely they tended to grouping. The aquatic environment at the three research stations still supports the growth of oysters. This study confirms that there has been a decline in the population, which is characterized by a decrease in the number of catches and a smaller size of oysters.